ENTERPRISE APPLICATION ARCHITECTURE FRAMEWORK PARKING INFORMATION SYSTEM USING TOGAF ADM (CASE STUDY : BRAYAN SHOPPING CENTRE ) - Aswati, Safrian; Fahmi, M. Irfan; Anwar, Khairil (IJRDO -Journal of Computer Science Engineering, 2016)
The Brayan Shopping Centre is a shopping center in the Medan which there are many consumers who visitevery day. It is an affects to increase the volume of vehicles on the court of Brayan Shopping Centre,because certainly the visitors who come to bring the vehicle. Data management boulevard parking vehiclesof visitors who really needs to do let alone the current technological developments are so rapid dataprocessing requires that every aspect has to be utilizing information technology and computerizedapplication form in order to provide the details. The application designed for data processing park vehicleson the Brayan Shopping Centre in the form of an information system that was created by applying aframework.Enterprise architecture enterprise architecture (EA) is a structured approach to describe anysystem needs so that it can be used to design and develop complex systems to be more modest. In the EArequired the use of modeling framework. With the framework, allows developers to design and develop thesystem, because the stages, methods or logical structure that has been provided by the framework. In thisresearch framework used is TOGAF. TOGAF provides a method which detail how to build and manage andimplement enterprise architecture and information systems called the Architecture Development Method(ADM).